Impacto da urbanização sobre as tartarugas verdes (Chelonia mydas) e seu potencial como sentinela da degradação costeira - Ferreira, Juliana Santos (2018)
The decline of green turtle (Chelonia mydas) populations, to the point that the species is considered "endangered" by the IUCN, results from decades of direct and indirect anthropogenic impacts. Present-day impacts appear particularly important for individuals in the juvenile stage that make intensive use of coastal regions where intense human activities have profundly altered coastal ecosystems. Therefore, the objective of this work was to a) evaluate the impact of environmental degradation on green turtle populations in areas with different levels of urbanization in order to b) establish parameters to use this species in its juvenile phase as an indicator of degradation of coastal areas. Night-light data obtained by satellite imagery was used as a proxy for urbanization level in six nonurbanized to highly urbanized areas along the Brazilian coast. Green turtle health parameters (severity of fibropapillomatosis, diet and body condition) were extrated from a database of previously collected data. Multiple regression analysis revealed that health responds negatively to urbanization (R2 = 0.29; p <0.01), so that the more urbanized the area, the worse the body condition (p <0.01), more severe the fibropapillomatosis (p = 0.03), and the lower the diversity of consumed items (p = 0.04). This significant response to local impacts indicates the potential use of green turtle as a sentinel of environmental quality. Habitat quality is quantifiable through the use of fibropapillomatosis severity scores and body conditions that are fast and easy to obtain and are strong indicators of green turtle health.